Dari Struktur Birokrasi Tradisional ke Model Adhocracy (Struktur Organisasi Inovatif) - Lesmana Rian Andhika (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
The large bureaucratic structure will cause a range of negative consequences, comprehensive changes required. Adhocracy is one option from the many models of re-bureaucratic structure. This model is seen as an antithesis of bureaucracy that is outside the formal bureaucratic structure. Adhocracy is also referred to as the modern organization structure, innovative organization that can adapt to the changing environment. The purpose of this research seeks to contribute its knowledge by exploring a variety of secondary data, multiply a couple arguing about the concept and the form of adhocracy in bureaucracy. Meta-theory is used as a research method, data reduction in deductive to draw conclusions. The results of this study reveal adhocracy needed in bureaucracy, bureaucratic structure changes are objective needs in the last decade to get a performance of bureaucracy is more effective for delivering a quality of public services.DOI: https://doi.org/10.26905/pjiap.v3i1.1809